ANALYSIS BETWEEN THE NUMBER OF ANTIHYPERTENSIVE WITH MEDICATION ADHERENCE IN END STAGE RENAL DISEASE - Ratnasari, Pande Made Desy; Yani, Ketut Lia Pran Anggar; Arini, Heny Dwi (Universitas Muhammadiyah Magelang, 2022)
End-Stage Renal Disease (ESRD) is a condition of severe renal damage associated with a higher incidence of hypertension that requires antihypertensive therapy to prevent the worsening disease. Therefore, patients who received more than two types of antihypertensives have affected medication adherence. This study aimed to analyze relationship between the number of antihypertensives and medication adherence in ESRD patients. The study was a cross-sectional design involving 77 participants selected by a purposive sampling technique at Outpatient Private Hospital Buleleng Bali in July-September 2020. Data were collected based on patient’s medical records and the Probabilistic Medication Adherence Scale (ProMAS) questionnaire. The inclusion criteria were ESRD patients aged ≥18 years, with hypertension history, taking the same antihypertensive for three months before the study, sign informed consent, and completed medical record data. Those who were a weak general condition and cognitive impairment were excluded from the study. Data were analyzed using a Kruskal-Wallis test. The results showed that overall, of patients were <65 years old (80.52%), male (70.13%), duration of ESRD <5 years (89.61%), primarily high school (57.14%), and without complications (57.1%). Most patients used a combination of two antihypertensives (35.07%), and 61.04% has a high medication adherence. There was no significant relationship between the number of antihypertensives and medication adherence (p=0.847). Nevertheless, it was still shown that the higher number of antihypertensives in ESRD patients was directly proportional to the lower medication adherence.